2016
DOI: 10.3349/ymj.2016.57.5.1271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Susceptibility of Mycoplasma hominis and Ureaplasma urealyticum in Pregnant Women

Abstract: Mycoplasma hominis (M. hominis) and Ureaplasma urealyticum (U. urealyticum) are important opportunistic pathogens that cause urogenital infections and complicate pregnancy. The aim of this study was to investigate the prevalence, effects on pregnancy outcomes, and antimicrobial susceptibilities of M. hominis and U. urealyticum. We tested vaginal swabs obtained from 1035 pregnant women for the presence of genital mycoplasmas between June 2009 and May 2014. The laboratory and clinical aspects of genital mycoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 16 publications
2
33
1
2
Order By: Relevance
“…Clarithromycin is another macrolide with good antibacterial activity against Ureaplasma spp. isolated from pregnant women who showed high susceptability (82.9–86.0%) to clarithromycin . A report showed that 3.7% of pregnant patients with U. parvum colonization who were not treated with antibiotics, such as clarithromycin, had preterm birth at less than 34 weeks of gestation and late abortion.…”
Section: Therapeutic Options For Genital Ureaplasma Infection In Pregmentioning
confidence: 99%
“…Clarithromycin is another macrolide with good antibacterial activity against Ureaplasma spp. isolated from pregnant women who showed high susceptability (82.9–86.0%) to clarithromycin . A report showed that 3.7% of pregnant patients with U. parvum colonization who were not treated with antibiotics, such as clarithromycin, had preterm birth at less than 34 weeks of gestation and late abortion.…”
Section: Therapeutic Options For Genital Ureaplasma Infection In Pregmentioning
confidence: 99%
“…or Ureaplasma spp. [ 45 ], rising resistance [ 46 ] and recent association with increased risk of cerebral palsy, epilepsy [ 42 , 47 ] as well as asthma and obesity [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Полученные за последние годы данные литературы свидетельствуют об увеличении частоты выявления урогенитальных микоплазм, резистентных к препаратам фторхинолонового ряда и макролидам, наиболее часто применяемым в терапии воспалительных заболеваний органов малого таза [3][4][5].…”
Section: Introductionunclassified